Paddy production planning in Kelantan using mixed integer programming / Nur Haifaa’ Maisarah Riduan and Nurain Nadhirah Adnan - Riduan, Nur Haifaa’ Maisarah; Adnan, Nurain Nadhirah (2022)
Lembaga Kemajuan Pertanian Kemubu (KADA) is one of the agricultural industries located in Kelantan that works on improving various crop advancement includes paddy cultivation. Since there is a large market for paddy production in Malaysia, the paddy producers frequently encountered by the issue of being unable to meet the demand of paddy in a profitable way due to the ongoing rise in input prices such as labor, land rent, and agricultural inputs. This paper proposes an application of Mixed Integer Linear Programming (MILP) to manage the paddy production planning in order to minimize cost of paddy production and maximize net profit of paddy production. The Mixed Integer Linear Programming (MILP) method is applied because there are constraints that need to be fulfilled on the problems. The mathematical model was developed to determine the minimum cost of paddy production and to obtain the optimal solution of maximize profit. The cost of raw materials, labours, machines, land rents, and the amount of paddy product sold (tonnes) were critically considered in this mathematical modelling. The result from the proposed model for the minimize cost model is RM6,532,648.76 while the maximize profit model is RM12,340,600.00. The findings indicate the proposed model could incorporate the essential resources which result in reducing the total manufacturing production cost at the same time maximize the profit.